Secondary school students’ knowledge of physiotherapy as a profession - Maduagwu, Stanley M.; Braimoh, Emelda; Muonwe, Chidile; Umeonwuka, Chuka; Ishaku, Cornelius M.; Modu, Ali Alhaji; Nwanne, Chiamaka Ann; Maduagwu, Beatrice C. (International Journal Of Community Medicine And Public Health, 2022)
Background: Physiotherapy plays a significant role in the health care system. The pursuit of a career in any profession by secondary school students depends largely on the availability of information about the practice and prospects of the profession. This study aimed at investigating whether secondary school students know about physiotherapy as a profession. Methods: This study was a cross-sectional survey involving eight hundred and two senior secondary school students in Maiduguri. Multi-stage and systematic random sampling techniques were used in selecting thirty schools in Maiduguri whose students participated in this study. A 37-item questionnaire from previous literature comprising of socio-demographic characteristics of participants, knowledge of participants about physiotherapy as a course, knowledge of participants about physiotherapists’ tasks and characteristics, and sources of their information about physiotherapy, was adapted for this study. Data were analysed using descriptive statistics. Results: Responses of eight hundred and two participants, 446 female and 356 males with a mean age of 16.90±2.22 were included in this study. More than half of the participants (59.1%) had a high knowledge of physiotherapy as a career. The most common sources of information about physiotherapy were from a family member (48.5%), a movie (54.7%), and the school career counsellor (54.5%). Conclusions: Half of the participants demonstrated a high level of knowledge of physiotherapy as a profession whereas a good number seemed to have little or no knowledge about the physiotherapy profession. The physiotherapy professional body should work towards increasing the level of knowledge of physiotherapy practice by creating avenues for career talks and awareness programs.